Jungian shadow of the unconscious in The Between and Come Closer - Akam, John Helvy (2017)
According to Jung, the archetype or the collective unconscious refers to human’s shared experiences that transcend generations and cultures, often projected onto myths, folktales, epics and other works in the form of repeated motives and character roles. One of such archetypes is the shadow archetype which refers to the repressed dark traits of one’s personality that has been unconsciously relegated into the unconscious mind. In older literary works, the shadow is often equated with the supernatural or monstrous characters. Over the course of time, as a result of the changing trend in horror fictions as well as critics consensus that the horror genre does not merit scholarly attention, studies on the shadow tend to disengage from horror elements in favor of focusing on realistic and grounded psychological issues. It is therefore an unsurprising fact that contemporary horror fictions are occasionally overlooked in scholarly studies. Two contemporary horror novels, The Between (1996) by Tananarive Due and Come Closer (2003) by Sara Gran are selected for this study. This study attempts to identify how the shadows manifest themselves in the novels and to investigate how the protagonists deal with their shadow. This study is conducted by identifying the shadow traits and the anima or animus complex experienced by the protagonists, Hilton and Amanda. Following the identification of these traits, the manifestation of the shadow can then be identified through projections of said traits. Then, the process to integrate the shadow is examined through the protagonists’ actions. By investigating their action, it can then be determined whether they are successful or unsuccessful in their individuation process. The analysis of the selected novels reveals that the shadow and the anima or animus of the protagonists manifest themselves as supernatural entities that are real for these characters, but these entities exist only because of their deteriorating psyche. In dealing with the manifestation, both protagonists failed to integrate their shadow because of their reluctance in facing their own dark sides. This study managed to create a bridge that connects the supernatural aspects of the shadow as observed in the studies of older texts and the psychological issues caused by the shadow that is more prevalent in studies of contemporary fictions.